The Relationship Between Trade Openness and Child and Youth Health in the Domain of Frequency: An Empirical Analysis For BRICS-T Countries - Ünlü, Atilla; Çelik, Süleyman (Inonu University, 2023)
The aim of the study is to examine the relationship between the phenomenon of commercial openness and child and youth health. The study sample consists of BRICS-T (Brazil, Russia, India, China, South Africa and Turkey) countries. The study was analyzed in the light of asymmetric components in the period between 1990-2021. ARDL (Auto Regressive Distributed Lag) bounds test approach was used for co-integration analysis between variables. The causality relationship of the variables was analyzed with the Breitung Candelon frequency domain method, and finally, OLS and FMOLS methods were used in parameter estimation. According to the parameter results, the increase in trade openness in BRICS-T countries has a reducing effect on child and youth mortality and contributes to the improvement of public health. © 2023, Journal of Inonu University Health Services Vocational School. All rights reserved.
FREKANS ALANINDA TİCARİ AÇIKLIK İLE ÇOCUK VE GENÇ SAĞLIĞI İLİŞKİSİ: BRICS-T ÜLKELERİ İÇİN AMPİRİK BİR ANALİZ
Keywords: Causality; Child mortality; Commercial opening; Teen mortality